Temporal and spatial flowering patterns in a Supramediterranean pasture-forest community in the Iberian Central System (Spain) = Patrón de floración temporal y espacial en un pasto Supramediterráneo del Sistema Central Ibérico (España) influenciado de forma heterogénea por la cobertura forestal - Minaya Santa Cruz, Miguel; Cebolla Lozano, Consuelo (Pastos, 2016)
ABSTRACTSpecies adjust their flowering throughout the annual cycle, showing both temporal and spatial patterns in the use of resources. Research examining temporal flowering dynamics and spatial flowering patterns within a Supramediterranean pasture is largely lacking, particularly within the Iberian Central System of Spain. Our aims were to establish an empirical flowering sequence throughout the annual cycle based on synchronously flowering species, and to investigate the relationship between local species flowering and environmental variables measured at different spatial points in a pasture-forest continuum.Two types of sampling were conducted, once weekly throughout one annual cycle, for 133 previously selected herbaceous species. First, the presence of flowering species was monitored. The Jaccard similarity coefficient was used to group the sampling dates as a function of the synchronously flowering species observed at each sampling timepoint. Secondly, the presence of flowering species and the variables soil temperature and edaphic humidity percentage were monitored in nine permanent plots placed in areas influenced to different degrees by the woody canopy.The temporal and spatial patterns inferred in this research contribute to explaining the singularity of the Supramediterranean pastures found in the Iberian Central System. The four flowering pulses assessed throughout the annual cycle allow us to make a first functional approximation to the natural rhythm of flowering that occurs in these communities. The spatial flowering pattern observed from February to July suggests the existence of a small-scale mosaic of microenvironments between the areas highly and scarcely affected by the forest canopy. This microenvironment segregation hypothesis would explain the synchrony of flowering of species with different environmental and chorological preferences. The temporal and the spatial flowering patterns postulated here would contribute to explaining the high richness of herbaceous species traditionally found in the few well-conserved Supramediterranean pasture – forest continuum ecosystems that still remain in the Iberian Central System of Spain.